Analysis on Growth Pattern and Economic Sectors in Bali Province - Dewa Gede Sidan Raeskyesa; Reinardus Adhiputra Suryandaru; Yohanes Berenika Kadarusman (Jurnal Ilmu Manajemen & Ekonomika, 2019)
In decentralization system, understanding the characteristics of region’s economy becomes necessary for productivity. In that regard, this descriptive study aims to describe the characteristics of the local economy in Balinese regencies and to identify the potential sectors to be developed therein. Using such methodologies as Klassen Typology, Location Quotient, Growth-Ratio Model, and Overlay analysis from year 2010 to 2016. As a result, we have found significant gap amongst regencies, where Badung and Denpasar are the most developed regencies, with high level both in growth rate and GDP per Capita. On the other hand, Klungkung, Jembrana, Bangli, Karangasem, and Tabanan are the least developed. Furthermore, it was found that most sectors in Bali are experiencing slow growth during the research period. By studying all the regencies in Bali province, this study not only enrich the existing literature but also recommend potential sectors from each region to be developed in order to reduce the development gap between regencies.